Power lithium ion battery coated with conductive adhesive on surface and preparation method of power lithium ion battery
By using surface-coated conductive glue and high-power physical vapor deposition technology on power lithium-ion batteries, the problems of current collector corrosion and slurry inhomogeneity are solved, the cycle performance and conductivity of the battery are significantly improved, and the overall battery is improved Performance and stability.
Patent Information
- Application Number
- CN202411540906.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
AI Technical Summary
Powered lithium-ion batteries are prone to corrosion in an electrochemical environment, resulting in reduced adhesion and poor battery performance. In addition, traditional slurry preparation methods cannot ensure uniform dispersion and stability, which affects the capacity and cycle stability of the battery.
Using surface coated conductive adhesives, including lithium manganate, graphite, electrolyte, polyethylene, conductive fillers and polymer binders, slurry is prepared through high-speed shearing machines and ultrasonic dispersers, and cured in a nitrogen environment, combined with High-power physical vapor deposition technology carbohydrate treatment to improve the adhesion and conductivity of the current collector.
It significantly improves the cycling performance, rate performance and conductivity of the battery, enhances the adhesion and corrosion resistance of the current collector coating, and improves the overall performance and stability of the battery.
Smart Images

Figure CN119230915A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, in particular to a power lithium-ion battery with a conductive adhesive coated on its surface and a preparation method thereof. Background Art
[0002] Power lithium-ion batteries are high-performance rechargeable batteries that are widely used in electric vehicles, electric bicycles, power tools, energy storage systems, and other fields that require high energy density and high power output. Compared with traditional lead-acid batteries and nickel-cadmium batteries, lithium-ion batteries have high energy density, which allows them to store more energy at the same volume and weight, thereby extending the range of electric equipment. At the same time, power lithium-ion batteries can provide high power output, meeting the needs of electric vehicles and power tools for instantaneous high currents, improving the performance of the equipment, and compared with traditional batteries such as lead-acid batteries, lithium-ion batteries are more environmentally friendly, reduce the emission of harmful substances, and cause less pollution to the environment.
[0003] However, existing power lithium-ion batteries still face some problems that need to be solved in actual use and preparation;
[0004] First, the current collector of power lithium-ion batteries is usually aluminum foil or copper foil, which is used to collect and conduct current. In the electrochemical environment of the battery, the surface of the current collector is prone to corrosion, especially under high-rate charge and discharge conditions. Corrosion not only affects the cycle life of the battery, but also reduces the adhesion between the active material and the current collector, thereby increasing the powder removal phenomenon and further reducing the performance and reliability of the battery. Traditional methods have failed to effectively solve the problems of corrosion and adhesion on the surface of the current collector, resulting in poor battery rate performance and cycle performance;
[0005] Secondly, when preparing battery slurry in the process of preparing power lithium-ion batteries, the uniform dispersion of active materials, conductive agents and binders is crucial. Traditional slurry preparation methods such as ordinary stirring often cannot ensure the uniform dispersion and stability of the slurry, resulting in uneven internal structure of the battery, affecting the capacity and cycle stability of the battery. In addition, the thickness and uniformity of the slurry are difficult to control during the coating process, resulting in insufficient conductivity and durability.
[0006] Finally, although lithium-ion batteries often use physical vapor deposition (PVD) technology to perform carbon coating in order to improve the conductivity and corrosion resistance of the current collector, the traditional PVD method often has poor coating adhesion, unsatisfactory conductivity and corrosion resistance, which affects the overall performance of the battery. The adhesion, conductivity and corrosion resistance of the current collector coating are important factors that determine battery performance and life, and there is a lot of room for improvement in this regard in the existing technology. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a power lithium-ion battery with a surface coated with a conductive adhesive and a preparation method thereof, which solves the problem that the surface of the current collector is prone to corrosion in the electrochemical environment of the battery.
[0008] To achieve the above purpose, the present invention is implemented through the following technical scheme: a power lithium ion battery with a conductive glue coated on the surface, comprising the following component materials: 15 to 30 parts of lithium manganese oxide, 10 to 25 parts of graphite, 20 to 40 parts of electrolyte, 5 to 15 parts of polyethylene, 10 to 20 parts of current collector, 5 to 15 parts of conductive filler, 5 to 15 parts of polymer binder, 20 to 40 parts of solvent, 0.2 to 2 parts of dispersant, 0.1 to 1 part of leveling agent, and 0.1 to 1 part of anti-settling agent.
[0009] Preferably, the conductive filler includes carbon black, graphite, and carbon nanotubes, and the addition ratio of the carbon black, graphite, and carbon nanotubes is 1:2:1.
[0010] Preferably, the polymer binder includes polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-propylene-diene monomer, and the addition ratio of polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-propylene-diene monomer is 2:3:1; the dispersant includes polyethylene glycol, polyacrylic acid, and nonylphenol polyoxyethylene ether, and the addition ratio of polyethylene glycol, polyacrylic acid, and nonylphenol polyoxyethylene ether is 2:1:1.
[0011] Preferably, the leveling agent includes silicone, polyurethane, and acrylates, and the addition ratio of the silicone, polyurethane, and acrylates is 2:1:1. The anti-settling agent includes bentonite, modified polyamide wax, and aluminum silicate, and the addition ratio of the bentonite, modified polyamide wax, and aluminum silicate is 3:1:2.
[0012] A method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface comprises the following steps:
[0013] S1. Material preparation: prepare lithium manganese oxide, graphite, electrolyte, polyethylene, current collector, conductive filler, polymer binder, solvent, dispersant, leveling agent, anti-settling agent;
[0014] S2. Preparation of conductive adhesive slurry: Use a high-speed shearing machine to mix carbon black, graphite, and carbon nanotubes for 3 minutes to 14 minutes, and add them to the solvent. Then add polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-propylene-diene monomer to the solvent in sequence, and use an ultrasonic disperser to disperse them evenly for 20 minutes to 30 minutes to form a slurry. Finally, add a dispersant, a leveling agent, and an anti-settling agent, and use a magnetic stirrer to stir for 30 minutes to 45 minutes.
[0015] S3, coating and curing: Use a sprayer to evenly coat the conductive adhesive on the surface of the current collector, put the coated current collector into a drying oven and add nitrogen to form an inert gas environment for heating and curing for 35 minutes to 57 minutes;
[0016] S4, carbon coating treatment: Use physical vapor deposition equipment to perform high-power carbon coating treatment on the surface of the current collector to further improve conductivity and corrosion resistance;
[0017] S5, prefabrication of positive and negative electrodes: coating the aluminum foil coated with conductive glue with lithium manganate slurry, using a coating machine to evenly coat and then dry to form a positive electrode, and then coating the copper foil coated with conductive glue with graphite slurry, using a coating machine to evenly coat and then dry to form a negative electrode;
[0018] S6. Battery assembly: On a winding machine or a laminating machine, the positive electrode, polyethylene and negative electrode are stacked in sequence, and wound or stacked into a battery cell structure. The battery cell is then placed in a liquid injection device to inject electrolyte, and is sealed in a sealing device for 30S to 60S.
[0019] Preferably, in the step S2, the rotation speed of the high-speed shearing machine is 3000 rpm to 5000 rpm, the power of the ultrasonic disperser is 400 W to 600 W, and the rotation speed of the magnetic stirrer is 800 rpm to 1200 rpm.
[0020] Preferably, in the step S3, the coating thickness of the sprayer is 10 μm-20 μm, and the temperature of the drying oven is 80° C. to 120° C.
[0021] Preferably, in the step S4, the temperature of the physical vapor deposition equipment is 400° C. to 600° C., and the operation time is 1 h to 2 h.
[0022] Preferably, in the step S5, the coating thickness of the coater is 50 μm-100 μm, and the drying time is 1 h to 2 h.
[0023] Preferably, in the step S6, the winding tension of the winding machine is 10N to 20N, the injection volume of the injection device is 20ML to 40ML, and the temperature of the sealing device is 150°C to 196°C.
[0024] The present invention provides a power lithium-ion battery with a conductive adhesive coated on the surface and a preparation method thereof. It has the following beneficial effects:
[0025] 1. The present invention prevents corrosion of the current collector surface under an electrochemical environment by coating the surface of the battery current collector with a conductive adhesive, thereby improving the adhesion between the active material and the current collector surface, reducing powder shedding under battery rate charge and discharge, reducing the impedance of the interface between the active material and the current collector, preventing the precipitation of impurities in the microbattery current collector, and preventing the precipitation of Cu2+ caused by over-discharge of the battery, thereby effectively improving the cycle performance and rate performance of the battery.
[0026] 2. The present invention adopts the combined use of a high-speed shearing machine and an ultrasonic disperser to ensure the uniform dispersion and stability of the slurry, thereby greatly improving the capacity and cycle stability of the battery. At the same time, the conductive adhesive slurry is coated by a precision sprayer and heated and cured in a nitrogen environment to ensure the uniformity and quality of the coating, thereby improving the conductivity and durability of the battery.
[0027] 3. The present invention uses high-power physical vapor deposition technology to perform carbon coating. Compared with traditional carbon coating methods, it significantly improves the adhesion, conductivity and corrosion resistance of the current collector coating and enhances the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The figure is a flow chart of the method steps of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1: Preparation of power lithium-ion battery using standard process
[0031] Specific steps:
[0032] S1. Material preparation: lithium manganese oxide: 25 parts, graphite: 20 parts, electrolyte: 30 parts, polyethylene: 10 parts, current collector: 15 parts, conductive filler (carbon black: 1.25 parts, graphite: 2.5 parts, carbon nanotubes: 1.25 parts), polymer binder (polyvinylidene fluoride: 2.5 parts, polytetrafluoroethylene: 3.75 parts, ethylene-propylene-diene monomer: 1.25 parts), solvent: 30 parts, dispersant (polyethylene glycol: 0.4 parts, polyacrylic acid: 0.2 parts, nonylphenol polyoxyethylene ether: 0.2 parts), leveling agent (organic silicon: 0.4 parts, polyurethane: 0.2 parts, acrylates: 0.2 parts), anti-settling agent (bentonite: 0.3 parts, modified polyamide wax: 0.1 parts, aluminum silicate: 0.2 parts);
[0033] S2, preparation of conductive adhesive slurry: mix carbon black, graphite and carbon nanotubes with a high-speed shearing machine (speed 4000 rpm) for 10 minutes, add solvent, add polyvinylidene fluoride, polytetrafluoroethylene and ethylene-propylene-diene monomer, use ultrasonic disperser (power 500 W) to disperse for 25 minutes, add dispersant, leveling agent and anti-settling agent, and stir with a magnetic stirrer (speed 1000 rpm) for 40 minutes;
[0034] S3, coating and curing: Use a sprayer (coating thickness 15 μm) to coat the conductive adhesive on the surface of the current collector, and cure it in a drying oven at 80° C. in a nitrogen environment for 45 minutes;
[0035] S4, carbon coating treatment: physical vapor deposition equipment performs carbon coating treatment at 500°C for 1.5 hours;
[0036] S5, positive and negative electrode prefabrication: positive electrode: apply lithium manganate slurry on aluminum foil coated with conductive glue and dry for 2 hours; negative electrode: apply graphite slurry on copper foil coated with conductive glue and dry for 2 hours;
[0037] S6, battery assembly: Use a winding machine to wind the positive electrode, polyethylene, and negative electrode (winding tension 15N), inject 35ml of electrolyte, seal the equipment at 175°C, and seal for 45 seconds;
[0038] Summarize:
[0039] This embodiment adopts standard ratios and process parameters to ensure stable performance and high conductivity of the battery and is suitable for large-scale production.
[0040] Example 2: Preparation of high energy density power lithium ion battery
[0041] Specific steps:
[0042] S1. Material preparation: lithium manganese oxide: 30 parts, graphite: 25 parts, electrolyte: 40 parts, polyethylene: 15 parts, current collector: 20 parts, conductive filler (carbon black: 1.5 parts, graphite: 3 parts, carbon nanotubes: 1.5 parts), polymer binder (polyvinylidene fluoride: 3 parts, polytetrafluoroethylene: 4.5 parts, ethylene-propylene-diene monomer: 1.5 parts), solvent: 40 parts, dispersant (polyethylene glycol: 0.6 parts, polyacrylic acid: 0.3 parts, nonylphenol polyoxyethylene ether: 0.3 parts), leveling agent (organic silicon: 0.6 parts, polyurethane: 0.3 parts, acrylates: 0.3 parts), anti-settling agent (bentonite: 0.45 parts, modified polyamide wax: 0.15 parts, aluminum silicate: 0.3 parts);
[0043] S3, preparation of conductive adhesive slurry: high-speed shearing machine (speed 4500rpm) mixed carbon black, graphite, carbon nanotubes for 12 minutes, and added solvent, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-propylene-diene monomer, using ultrasonic disperser (power 550W) to disperse for 28 minutes, adding dispersant, leveling agent, anti-settling agent, and stirring with magnetic stirrer (speed 1100rpm) for 45 minutes;
[0044] S3, coating and curing: Use a sprayer (coating thickness 18 μm) to coat the conductive adhesive on the surface of the current collector, and cure it in a drying oven at 90° C. in a nitrogen environment for 50 minutes;
[0045] S4, carbon coating treatment: physical vapor deposition equipment performs carbon coating treatment at 550°C for 1.8 hours;
[0046] S5. Prefabrication of positive and negative electrodes: Positive electrode: apply lithium manganate slurry on aluminum foil coated with conductive glue and dry for 1.5 hours; negative electrode: apply graphite slurry on copper foil coated with conductive glue and dry for 1.5 hours.
[0047] S6. Battery assembly: Use a laminating machine to stack the positive electrode, polyethylene, and negative electrode into a battery cell structure, inject 40 ml of electrolyte, seal the equipment at 180°C, and seal for 50 seconds.
[0048] Summarize:
[0049] This embodiment is suitable for applications requiring high energy density, and improves the energy density of the battery by increasing the material ratio and optimizing process parameters.
[0050] Example 3: Preparation of fast charge and discharge power lithium ion battery
[0051] Specific steps:
[0052] S1. Material preparation: lithium manganese oxide: 20 parts, graphite: 15 parts, electrolyte: 25 parts, polyethylene: 10 parts, current collector: 15 parts, conductive filler (carbon black: 1 part, graphite: 2 parts, carbon nanotube: 1 part), polymer binder (polyvinylidene fluoride: 2 parts, polytetrafluoroethylene: 3 parts, ethylene-propylene-diene monomer: 1 part), solvent: 25 parts, dispersant (polyethylene glycol: 0.4 parts, polyacrylic acid: 0.2 parts, nonylphenol polyoxyethylene ether: 0.2 parts), leveling agent (organic silicon: 0.4 parts, polyurethane: 0.2 parts, acrylates: 0.2 parts), anti-settling agent (bentonite: 0.3 parts, modified polyamide wax: 0.1 parts, aluminum silicate: 0.2 parts);
[0053] S2, preparation of conductive adhesive slurry: high-speed shearing machine (speed 3500rpm) mixed carbon black, graphite, carbon nanotubes for 8 minutes, and added solvent, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-propylene-diene monomer, using ultrasonic disperser (power 450W) to disperse for 22 minutes, adding dispersant, leveling agent, anti-settling agent, and stirring with magnetic stirrer (speed 900rpm) for 35 minutes;
[0054] S3, coating and curing: Use a sprayer (coating thickness 12 μm) to coat the conductive adhesive on the surface of the current collector, and cure it in a drying oven at 85° C. in a nitrogen environment for 40 minutes;
[0055] S4, carbon coating treatment: physical vapor deposition equipment performs carbon coating treatment at 450°C for 1.2 hours;
[0056] S5, positive and negative electrode prefabrication: positive electrode: apply lithium manganate slurry on aluminum foil coated with conductive glue and dry for 1 hour; negative electrode: apply graphite slurry on copper foil coated with conductive glue and dry for 1 hour;
[0057] S6. Battery assembly: Use a winding machine to wind the positive electrode, polyethylene, and negative electrode (winding tension 12N), inject 30ml of electrolyte, seal the equipment at a temperature of 160°C, and seal for 40 seconds.
[0058] Summarize:
[0059] This embodiment optimizes the charging and discharging speed and is suitable for applications such as power tools and electric vehicles that require fast charging and discharging.
[0060] Example 4: Preparation of a power lithium-ion battery adapted to low temperature environments
[0061] Specific steps:
[0062] S1. Material preparation: lithium manganese oxide: 15 parts, graphite: 10 parts, electrolyte: 20 parts, polyethylene: 5 parts, current collector: 10 parts, conductive filler (carbon black: 0.75 parts, graphite: 1.5 parts, carbon nanotubes: 0.75 parts), polymer binder (polyvinylidene fluoride: 1.5 parts, polytetrafluoroethylene: 2.25 parts, ethylene-propylene-diene monomer: 0.75 parts), solvent: 20 parts, dispersant (polyethylene glycol: 0.3 parts, polyacrylic acid: 0.15 parts, nonylphenol polyoxyethylene ether: 0.15 parts), leveling agent (organic silicon: 0.3 parts, polyurethane: 0.15 parts, acrylates: 0.15 parts), anti-settling agent (bentonite: 0.2 parts, modified polyamide wax: 0.07 parts, aluminum silicate: 0.13 parts);
[0063] S2, preparation of conductive adhesive slurry: mix carbon black, graphite and carbon nanotubes with a high-speed shearing machine (speed 3000 rpm) for 7 minutes, add solvent, add polyvinylidene fluoride, polytetrafluoroethylene and ethylene-propylene-diene monomer, use ultrasonic disperser (power 400 W) to disperse for 20 minutes, add dispersant, leveling agent and anti-settling agent, and stir with magnetic stirrer (speed 800 rpm) for 30 minutes;
[0064] S3, coating and curing: Use a sprayer (coating thickness 10 μm) to coat the conductive adhesive on the surface of the current collector, and cure it in a drying oven at 80° C. in a nitrogen environment for 35 minutes;
[0065] S4, carbon coating treatment: physical vapor deposition equipment performs carbon coating treatment at 400°C for 1 hour;
[0066] S5, positive and negative electrode prefabrication: positive electrode: apply lithium manganate slurry on aluminum foil coated with conductive glue and dry for 1.5 hours; negative electrode: apply graphite slurry on copper foil coated with conductive glue and dry for 1.5 hours;
[0067] S6. Battery assembly: Use a laminating machine to stack the positive electrode, polyethylene, and negative electrode into a battery cell structure, inject 25 ml of electrolyte, seal the equipment at a temperature of 150°C, and seal for 30 seconds.
[0068] Summarize:
[0069] This embodiment optimizes the material and process parameters for low temperature environments, ensuring stable performance of the battery under low temperature conditions, and is suitable for electric equipment in cold regions.
[0070] Example 5: Preparation of high-safety power lithium-ion battery
[0071] Specific steps:
[0072] S1. Material preparation: lithium manganese oxide: 25 parts, graphite: 15 parts, electrolyte: 30 parts, polyethylene: 10 parts, current collector: 15 parts, conductive filler (carbon black: 1.25 parts, graphite: 2.5 parts, carbon nanotubes: 1.25 parts), polymer binder (polyvinylidene fluoride: 2.5 parts, polytetrafluoroethylene: 3.75 parts, ethylene-propylene-diene monomer: 1.25 parts), solvent: 30 parts, dispersant (polyethylene glycol: 0.4 parts, polyacrylic acid: 0.2 parts, nonylphenol polyoxyethylene ether: 0.2 parts), leveling agent (organic silicon: 0.4 parts, polyurethane: 0.2 parts, acrylates: 0.2 parts), anti-settling agent (bentonite: 0.3 parts, modified polyamide wax: 0.1 parts, aluminum silicate: 0.2 parts);
[0073] S2, preparation of conductive adhesive slurry: high-speed shearing machine (speed 4500rpm) mixed carbon black, graphite, carbon nanotubes for 10 minutes, and added solvent, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-propylene-diene monomer, using ultrasonic disperser (power 500W) to disperse for 25 minutes, adding dispersant, leveling agent, anti-settling agent, using magnetic stirrer (speed 1000rpm) to stir for 40 minutes;
[0074] S3, coating and curing: Use a sprayer (coating thickness 15 μm) to coat the conductive adhesive on the surface of the current collector, and cure it in a drying oven at 90° C. in a nitrogen environment for 50 minutes;
[0075] S4, carbon coating treatment: physical vapor deposition equipment performs carbon coating treatment at 550°C for 1.5 hours;
[0076] S5, positive and negative electrode prefabrication: positive electrode: apply lithium manganate slurry on aluminum foil coated with conductive glue and dry for 2 hours; negative electrode: apply graphite slurry on copper foil coated with conductive glue and dry for 2 hours;
[0077] S6. Battery assembly: Use a winding machine to wind the positive electrode, polyethylene, and negative electrode (winding tension 15N), inject 35ml of electrolyte, seal the equipment at a temperature of 175°C, and seal for 45 seconds.
[0078] Summarize:
[0079] This embodiment significantly improves the safety performance of the battery by optimizing materials and process parameters, and is suitable for application scenarios with high safety requirements, such as aviation and medical equipment.
[0080] Summary:
[0081] Through the above five embodiments, it can be seen that each process and parameter adjustment is optimized for a specific application scenario, thereby improving the specific performance indicators of the power lithium-ion battery. Each embodiment has its own unique advantages and scope of application, which respectively improves the stability, energy density, charge and discharge speed, low temperature adaptability and safety of the battery. In general, by adjusting the material ratio and process parameters, the diversified application of power lithium-ion batteries can be achieved to meet the needs of different fields.
[0082] Test experiment 1: Capacity test
[0083] step:
[0084] S1. Fully charge the battery of each embodiment;
[0085] S2. At standard temperature (25°C), discharge at a discharge rate of 0.5C and record the discharge time;
[0086] S3. Calculate the battery capacity.
[0087] data:
[0088] Example Capacity (mAh) Embodiment 1 3000 Embodiment 2 3200 Embodiment 3 2900 Embodiment 4 2800 Embodiment 5 3050
[0089] Result analysis:
[0090] The capacity of the second embodiment is the highest, which is suitable for high energy density requirements; the capacity of the fourth embodiment is the lowest, but considering its low temperature characteristics, it still has its applicable scenarios.
[0091] Test experiment 2: Energy density test
[0092] step:
[0093] S1. Measure the weight of the battery of each embodiment;
[0094] S2. Calculate the energy density (Wh / kg) using the capacity test results.
[0095] data:
[0096]
[0097] Result analysis:
[0098] The energy density of Example 2 is the highest, and that of Example 4 is the lowest, but still within a reasonable range.
[0099] Test experiment three: charge and discharge rate test
[0100] step:
[0101] S1, fully charging the battery of each embodiment at 1C, 2C, and 5C charging rates;
[0102] S2. Discharge at the same rate and record the charging and discharging time.
[0103] data:
[0104]
[0105]
[0106] Result analysis:
[0107] Embodiment 3 performs best in terms of rapid charging and discharging, and is suitable for applications with high power requirements; Embodiment 4 has a lower charging and discharging rate, but considering its low temperature characteristics, it still has certain advantages.
[0108] Test experiment 4: low temperature performance test
[0109] step:
[0110] S1. Place the battery in a -20℃ environment and stabilize it for 24 hours.
[0111] S2. Test at a charge and discharge rate of 0.5C and record the charge and discharge capacity.
[0112] data:
[0113]
[0114]
[0115] Result analysis:
[0116] The fourth embodiment performs best in low temperature environments, significantly higher than other embodiments, and is suitable for cold environment applications.
[0117] Test experiment 5: safety test
[0118] step:
[0119] S1. Perform overcharge, short circuit and puncture tests on the battery of each embodiment to observe the safety response of the battery.
[0120] data:
[0121] Example Overcharge reaction Short circuit reaction Acupuncture reaction Embodiment 1 Stablize Stablize Stablize Embodiment 2 Stablize Stablize Slight swelling Embodiment 3 Mild fever Mild fever Slight swelling Embodiment 4 Stablize Stablize Stablize Embodiment 5 Stablize Stablize Stablize
[0122] Result analysis:
[0123] Embodiments 4 and 5 performed best in the safety test, especially embodiment 4 showed excellent comprehensive performance.
[0124] Summary:
[0125] Capacity and energy density: Example 2 performs best in terms of capacity and energy density and is suitable for applications requiring high energy density.
[0126] Charge and discharge rate: Example 3 has the best charge and discharge rate and is suitable for applications with high power requirements.
[0127] Low temperature performance: Example 4 has excellent low temperature performance and is suitable for cold environments.
[0128] Security: Embodiment 4 and Embodiment 5 performed best in the security test and are suitable for application scenarios with high security requirements.
[0129] Comparative experiment 1: Research on polymer blended conductive adhesive materials
[0130] Existing technical solution: In the prior art, a single type of conductive adhesive material is often used for coating batteries. Although this method is simple, it may be insufficient in terms of conductivity, mechanical properties and durability.
[0131] Technical solution of the present invention: The present invention adopts polymer blended conductive adhesive material, including polyvinylidene fluoride, polytetrafluoroethylene and ethylene-propylene-diene monomer, which are blended in a ratio of 2:3:1 to improve conductivity and durability.
[0132] Comparison process design:
[0133] S1. Material preparation:
[0134] Existing technology: single PVDF or PTFE;
[0135] The present invention: PVDF, PTFE and EPDM are blended;
[0136] S2. Slurry preparation:
[0137] The same high-speed shearing and ultrasonic dispersion conditions (high-speed shearing machine speed 4000 rpm, ultrasonic disperser power 500 W, dispersion for 25 minutes);
[0138] S3, performance test:
[0139] Test conductivity, mechanical properties and durability.
[0140] Experimental data:
[0141]
[0142] Result analysis:
[0143] The blended conductive adhesive of the present invention is superior to the prior art in terms of conductivity, mechanical properties and durability, and significantly improves the performance of power lithium-ion batteries.
[0144] Comparative experiment 2: Study on slurry preparation process system
[0145] Prior art solution: In the prior art, a conventional agitator and a simple mixing method are usually used to prepare the slurry, which results in poor slurry uniformity and affects battery performance.
[0146] Technical solution of the present invention: The present invention adopts the combined use of a high-speed shearing machine and an ultrasonic disperser to ensure uniform dispersion of the slurry, thereby improving the uniformity and stability of the slurry.
[0147] Comparison process design:
[0148] S1. Material preparation:
[0149] Prior art: conventional agitator (rotation speed 800 rpm, stirring time 30 minutes);
[0150] The present invention: a high-speed shearing machine (rotation speed 4000rpm, shearing for 10 minutes) and an ultrasonic disperser (power 500W, dispersion for 25 minutes);
[0151] S2. Performance test:
[0152] The slurry was tested for uniformity, particle size distribution, and battery performance.
[0153] Experimental data:
[0154]
[0155] Result analysis:
[0156] The slurry preparation process of the present invention significantly improves the uniformity and particle size distribution of the slurry, thereby improving the capacity and cycle stability of the battery.
[0157] Comparative experiment 3: Study on coating and curing process technology
[0158] Existing technical solutions: In the existing technology, a simple coating method and a conventional heating curing method are usually used, and the coating thickness and uniformity are poor, which affects the conductivity and durability.
[0159] Technical solution of the present invention: The present invention adopts a precision sprayer for uniform coating, and heats and cures in an inert gas (nitrogen) environment to ensure the uniformity and quality of the coating.
[0160] Comparison process design:
[0161] S1. Coating and curing:
[0162] Existing technology: simple coating (coating thickness 20 μm), conventional heating curing (curing in air environment at 90°C for 30 minutes);
[0163] The present invention: coating by precision spraying machine (coating thickness 15 μm), heating and curing in nitrogen environment (curing at 90° C. for 50 minutes);
[0164] S2. Performance test:
[0165] Test coating uniformity, conductivity and durability.
[0166] Experimental data:
[0167]
[0168] Result analysis:
[0169] The coating and curing process of the present invention significantly improves the uniformity and conductivity of the coating and enhances the durability of the battery.
[0170] Summary: Through the test experiments of the embodiments and the comparative experiments with the prior art, it is shown that the power lithium-ion battery with conductive adhesive coated on the surface of the present invention and the preparation method thereof have significant advantages in many aspects. Example 2 performs best in capacity and energy density, and is suitable for applications with high energy requirements; Example 3 performs best in charge and discharge rate, and is suitable for high power applications; Example 4 performs well in low temperature performance and safety tests, and is suitable for applications in cold environments and with high safety requirements; in the comparative experiments, the polymer blended conductive adhesive material, advanced slurry preparation process, precise coating and curing process, and high-power PVD carbon coating technology used in the present invention have significantly improved the conductivity, mechanical properties, durability, and overall performance of the battery, which are superior to the prior art, and fully demonstrate the comprehensive advantages of the present invention in improving the performance and stability of power lithium-ion batteries.
[0171] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A power lithium-ion battery with a conductive adhesive coated on the surface, characterized in that: The invention comprises the following components: 15 to 30 parts of lithium manganese oxide, 10 to 25 parts of graphite, 20 to 40 parts of electrolyte, 5 to 15 parts of polyethylene, 10 to 20 parts of current collector, 5 to 15 parts of conductive filler, 5 to 15 parts of polymer binder, 20 to 40 parts of solvent, 0.2 to 2 parts of dispersant, 0.1 to 1 part of leveling agent and 0.1 to 1 part of anti-settling agent.
2. A power lithium-ion battery with a conductive adhesive coated on the surface according to claim 1, characterized in that: The conductive filler includes carbon black, graphite and carbon nanotubes, and the addition ratio of the carbon black, graphite and carbon nanotubes is 1:2:
1.
3. A power lithium-ion battery with a conductive adhesive coated on the surface according to claim 1, characterized in that: The polymer binder includes polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-propylene-diene monomer, and the addition ratio of the polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-propylene-diene monomer is 2:3:
1. The dispersant includes polyethylene glycol, polyacrylic acid, and nonylphenol polyoxyethylene ether, and the addition ratio of the polyethylene glycol, polyacrylic acid, and nonylphenol polyoxyethylene ether is 2:1:
1.
4. A power lithium-ion battery with a conductive adhesive coated on the surface according to claim 1, characterized in that: The leveling agent includes silicone, polyurethane, and acrylates, and the addition ratio of the silicone, polyurethane, and acrylates is 2:1:
1. The anti-settling agent includes bentonite, modified polyamide wax, and aluminum silicate, and the addition ratio of the bentonite, modified polyamide wax, and aluminum silicate is 3:1:
2.
5. A method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface, according to the power lithium-ion battery with a conductive adhesive coated on the surface according to claims 1-4, characterized in that: The following steps are involved: S1. Material preparation: prepare lithium manganese oxide, graphite, electrolyte, polyethylene, current collector, conductive filler, polymer binder, solvent, dispersant, leveling agent, anti-settling agent; S2. Preparation of conductive adhesive slurry: Use a high-speed shearing machine to mix carbon black, graphite, and carbon nanotubes for 3 minutes to 14 minutes, and add them to the solvent. Then add polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-propylene-diene monomer to the solvent in sequence, and use an ultrasonic disperser to disperse them evenly for 20 minutes to 30 minutes to form a slurry. Finally, add a dispersant, a leveling agent, and an anti-settling agent, and use a magnetic stirrer to stir for 30 minutes to 45 minutes. S3, coating and curing: Use a sprayer to evenly coat the conductive adhesive on the surface of the current collector, put the coated current collector into a drying oven and add nitrogen to form an inert gas environment for heating and curing for 35 minutes to 57 minutes; S4, carbon coating treatment: Use physical vapor deposition equipment to perform high-power carbon coating treatment on the surface of the current collector to further improve conductivity and corrosion resistance; S5, prefabrication of positive and negative electrodes: coating the aluminum foil coated with conductive glue with lithium manganate slurry, using a coating machine to evenly coat and then dry to form a positive electrode, and then coating the copper foil coated with conductive glue with graphite slurry, using a coating machine to evenly coat and then dry to form a negative electrode; S6. Battery assembly: On a winding machine or a laminating machine, the positive electrode, polyethylene and negative electrode are stacked in sequence, and wound or stacked into a battery cell structure. The battery cell is then placed in a liquid injection device to inject electrolyte, and is sealed in a sealing device for 30S to 60S.
6. The method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface according to claim 5, characterized in that: In the step S2, the rotation speed of the high-speed shearing machine is 3000 rpm to 5000 rpm, the power of the ultrasonic disperser is 400 W to 600 W, and the rotation speed of the magnetic stirrer is 800 rpm to 1200 rpm.
7. The method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface according to claim 5, characterized in that: In the step S3, the coating thickness of the sprayer is 10 μm-20 μm, and the temperature of the drying oven is 80° C.-120° C.
8. The method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface according to claim 5, characterized in that: In the step S4, the temperature of the physical vapor deposition equipment is 400° C. to 600° C., and the operation time is 1 hour to 2 hours.
9. The method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface according to claim 5, characterized in that: In the step S5, the coating thickness of the coater is 50 μm-100 μm, and the drying time is 1 h to 2 h.
10. The method for preparing a power lithium-ion battery with a conductive adhesive coated on the surface according to claim 5, characterized in that: In the step S6, the winding tension of the winding machine is 10N to 20N, the injection volume of the injection device is 20ML to 40ML, and the temperature of the sealing device is 150°C to 196°C.
